2017
DOI: 10.1093/aje/kwx054
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking and Risk of Incident Rosacea in Women

Abstract: The relationship between smoking and rosacea is poorly understood. We aimed to conduct the first cohort study to determine the association between smoking and risk of incident rosacea. We included 95,809 women from Nurses' Health Study II (1991-2005). Information on smoking was collected biennially during follow-up. Information on history of clinician-diagnosed rosacea and year of diagnosis was collected in 2005. We used Cox proportional hazards models to estimate age- and multivariable-adjusted hazard ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…A single cohort study from the United States has examined the association between cigarette smoking and the risk of rosacea. 14 This study has found that compared with never smoking, an increased risk of rosacea is associated with past smoking but a decreased risk associated with current smoking. However, the cohort consisted entirely of American female nurses, which might reduce the generalizability of the study's results.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…A single cohort study from the United States has examined the association between cigarette smoking and the risk of rosacea. 14 This study has found that compared with never smoking, an increased risk of rosacea is associated with past smoking but a decreased risk associated with current smoking. However, the cohort consisted entirely of American female nurses, which might reduce the generalizability of the study's results.…”
Section: Introductionmentioning
confidence: 77%
“…In addition to the inconsistent results, the case–control design of these studies is subject to several potential sources of bias. A single cohort study from the United States has examined the association between cigarette smoking and the risk of rosacea 14 . This study has found that compared with never smoking, an increased risk of rosacea is associated with past smoking but a decreased risk associated with current smoking.…”
Section: Introductionmentioning
confidence: 99%
“…However, there might also exist true sex‐specific differences as seen for migraine, a condition that has been linked to rosacea . Moreover, the overall higher prevalence of male smokers could affect the rosacea prevalence estimates, as a recent study showed that active smoking is associated with a lower prevalence of rosacea, possibly due to vasoconstriction . Ultraviolet irradiation is known to worsen the symptoms of rosacea, and actinic skin damage was shown to be associated with an increased prevalence of rosacea .…”
Section: Discussionmentioning
confidence: 99%
“…We examined the association between alcohol intake and risk of rosacea stratified by smoking status 19 . To address the concern of reverse-causation bias, a 4-year lag analysis was conducted by excluding rosacea cases documented within the first four years of each updated assessment of alcohol intake.…”
Section: Methodsmentioning
confidence: 99%